Kegiatan Keagamaan Sebagai Upaya dalam Pencegahan Kenakalan Remaja: Studi pada Pesantren Mahasiswa - Abdul Basith; Muhammad Asriyanto (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Juvenile delinquency today occurs regardless of the social status of society. Juvenile delinquency has developed into a problem that disturbs society and needs to be handled seriously. Efforts to control juvenile delinquency must continue to minimise juvenile delinquency's development in society. Therefore, this research aims to discover the religious activities carried out by the student boarding school of Sultan Aji Muhammad Idris State Islamic University (UINSI) Samarinda to prevent juvenile delinquency. The research method used in this study uses a qualitative approach. Data collection using interviews, observation, and documentation. Data analysis techniques by reducing data, presenting data, and verification or conclusion drawing. The results are that religious activities carried out in student pesantren are one of the efforts to prevent juvenile delinquency, especially among students. Activities carried out in student pesantren include ta'lim afkar, which is filled by ustadz and ustadzah in the pesantren. Muhadharah activities are carried out in rotation by students. The third is the Al-Qur'an tadarus activity, and the last is studying the Al-Qur'an with the book Tafsir Jalalin.